A Study of School Teacher’s Perspective on National Education Policy 2020 - Sharma, Smriti; Akalamkam, Kalyani (Voices of Teachers and Teacher Educators, 2021)
The National Education Policy (NEP) released in 2020 has been the topic of much public debate ever since the draft of the same was circulated in the wider public in 2019. Responses to the policy have been mixed with the policy being hailed as a commendable reform on one side and critics questioning the policy for its commitment to universal and equitable education on the other. Much of these deliberations in the public forums, however, have been confined to discussions amongst academicians and scholars. Given that teachers are key stakeholders in the educational reforms, the present study attempted to find out school teachers’ understanding of the NEP 2020 policy and their perception and opinion of the same. The research is broadly rooted in critical theory and the methodology is mixed methods research. Data was collected from 151 school teachers through the use of an online questionnaire. The analysis of the data is presented in four broad themes –‘early childhood care and education’, ‘curriculum and pedagogy’, ‘assessment’, ‘governance and systemic issues’. The findings reveal varying degrees of agreement of school teachers on these aspects of the NEP 2020 policy. Triangulation with qualitative data highlights teachers’ apprehensions with respect to implementation of the policy. Statistically, no significant differences were found in the opinions of government and private school teachers.